Rainfall Patterns in Konawe Islands Regency: Trends and Implications for Health - Hariati Lestari; Selvi Safitri; Aurel Amelia Putri Taoha; Dernayun; Ihsan Adi Sasono Sasono (Journal of Health Science and Pharmacy, 2025)
Background: Climate refers to long-term weather patterns that significantly impact human life. In Indonesia, there are three types of rainfall patterns: equatorial, monsoonal, and local. Unlike other areas in Southeast Sulawesi that have entered the dry season, the highest rainfall in Konawe Islands Regency typically occurs in May and June. This phenomenon is influenced by wind patterns that carry water vapor from Asia and the Pacific Ocean. Conversely, when winds blow from the east, particularly from Australia, dry season conditions prevail. The climate in this region has become increasingly complex due to unpredictable weather changes. Objective: This study aims to identify and analyze the factors contributing to rainfall in Konawe Islands Regency. Method: A quantitative approach was employed, utilizing measurable and statistically analyzable data. Results: The average annual rainfall in Konawe Islands Regency is 1,929.2 mm, with an average of 141 rainy days per year. Conclusion: Konawe Islands Regency experiences an average annual rainfall of 1,929.2 mm and approximately 141 rainy days. Rainfall patterns in the area are influenced by climatic conditions, topography, and the interaction of air masses. Keywords: Humans, Seasons, Wind, Weather, Indonesia